Effectiveness of Online Job Seeking Card (AK-1) Production Services at the Bandung District Employment Office - Raya Mustiraya; Atik Rochaeni (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2024)
This study investigates the effectiveness of the Online Job Seeker Card (Ak-1) services at the Bandung Regency Manpower Office. The urgency of this research stems from the need to enhance public awareness and the efficiency of service delivery. The objectives are to identify the effectiveness, obstacles, and efforts related to these services. The research employs a qualitative approach with a case study method. Data were collected through in-depth interviews, field observations, and document analysis. Findings indicate that despite timely service delivery, poor program socialization has led to low public awareness and suboptimal service impact, such as inefficient job distribution. Recommendations include increasing socialization efforts, improving inter-agency coordination, and upgrading the service platform to mobile applications to enhance accessibility for job seekers